Transgender Adaptation Strategies to Community Social Construction in Padang City - Putri Lenggogeni; Junaidi Indrawadi (Science and Environmental Journal for Postgraduate, 2021)
This research is a study of transgender people who carry out adaptation strategies to the social construction ofsociety in Padang City, by taking a case study in the West Padang location. This study describes atransgender adaptation strategy that aims to 1) analyze the meaning of transgender people on their genderidentity; 2) analyze the social construction of the community towards transgender and 3) analyze thetransgender strategy in adapting to the social construction of the community. Withdrawal of informants isdone by purposive sampling. The method used by the author is descriptive qualitative. Data collectiontechniques used are observation, interviews, and documentation. The results showed that 1) the meaning oftransgender women for their gender identity: a) as a woman; b) wanting to look beautiful in the eyes of thecommunity; and c) not hiding as a transvestite. So the meaning for transgender is as a choice because theywant to be recognized for their existence, there is a sexual desire if they become a woman, inner satisfaction,and pleasure in themselves; 2) gender social construction of transgender people is seen from: a) as peoplewho have deviant behavior; b) violating values and norms; c) amused, uncomfortable, uncomfortable withtransgender; d) fear of the impact of transgender on normal children, e) labeling transgender. This pointconcludes that the existence of transgender in the community initially received social pressures that madetheir mental patience tested, but over time slowly they (transgender) could be accepted well in society; 3)transgender strategies in adapting to the community environment: a) interact well; b) adjust the appearance;c) maintain attitudes and behavior. The strategy of transgender is to be able to interact in the environment byassociating and interacting with the community, besides that transgender also respect and uphold the valuesof maintaining ethics, mutual respect, both among teenagers, children and parents, so that later goodrelationships will be created.